Analysis of The Impact of Late Arrival at School on The Focus Of Early Childhood - Devi Febriana Romadhoniah; Ezif Rizqi Imtihana (Manunggal Halim Jaya, 2026)
Delayed attendance at the Early Childhood Education (ECE) level is often regarded as merely an administrative issue, whereas it has the potential to disrupt children’s cognitive stability during the golden age. This study aims to analyze the impact of lateness on children’s learning focus at TK Negeri Pembina Ngadirojo. Using a descriptive qualitative method with a purposive sampling technique, the study focuses observations on two subjects with the highest levels of lateness. The research findings, obtained through a questionnaire instrument, indicate that lateness is predominantly influenced by internal factors (scores 12–15), such as poor time management due to gadget use, compared to external factors (scores 6–8). Observational findings confirm that lateness triggers a phenomenon of “attention interruption,” in which children lose the momentum of initial apperception, resulting in reduced concentration throughout the learning process. This study contributes to the development of score-based intervention strategies for ECE educators to mitigate dysfunctions in domestic routines from an early stage.